Detection of Candidatus Bartonella odocoilei n. sp. in Lipoptena mazamae associated with white‐tailed deer in Campeche, Mexico. Issue 4 (25th June 2021) - Lozano‐Sardaneta, Y. N.; Blum‐Domínguez, S.; Huerta, H.; Tamay‐Segovia, P.; Fernández‐Figueroa, E. A.; Becker, I.; Sánchez‐Montes, S.
Abstract: The deer ked Lipoptena mazamae (Diptera: Hippoboscidae) (Róndani), is a blood‐feeding obligate ectoparasite of several species of deer and brocket. However, at present little information is available about its role as a vector of hemoparasites. Nonetheless, it is considered a competent vector for the transmission of Bartonella species. The aim of this study was performing the morphological and molecular identification of ked flies and to carry out the detection of Bartonella . We collected specimens from Chiná, Campeche, Mexico associated with white‐tailed deer. Using polymerase chain reaction (PCR), of COI, gltA and rpoB genes, we were able to obtain the first barcode for L. mazamae from Mexico and identified a new species of Bartonella which was found with a prevalence of 73%. The data obtained in this study confirmed the presence of L. mazamae associated with white‐tailed deer and its possible role as vector of Candidatus Bartonella odocoilei n. sp. in Mexico and we considered that it may also be present in white‐tailed deer populations in the U.S.A. Additional investigations into Bartonella species associated with deer ked could provide further insight into their pathogenicity and its role as a zoonotic agent. Abstract : The deer ked Lipoptena mazamae was identified using the COI gene for the first time for Mexico. Bartonella sp. was detected in deer ked in Campeche; using rpoB and gltA genes, we detected a new linage temporarily named as Candidatus Bartonella odocoilei. The role of Lipoptena mazamae in the transmission of Candidatus Bartonella odocoilei, in Campeche is very probable, however, additional entomological surveys are necessary.